IW Berlin economic outlook: Summer upswing to follow winter slump - Guido Baldi; Paul Berenberg-Gossler; Hella Engerer; Simon Junker; Konstantin Kholodilin; Frederik Kurcz; Laura Pagenhardt (DIW Weekly Report, 2022)
The Omicron wave of the coronavirus has impacted economies worldwide, resulting in a bleak winter. Although restrictions on economic and public life have been less severe than at the beginning of 2021 in many places-mainly due to the progress of vaccination campaigns-and there are prospects of easing restrictions in Germany as well, the labor shortage caused by the current rates of infection is noticeable. Nevertheless, the economic recovery in Germany has only been interrupted- as soon as the pandemic subsides in the spring, there will be a marked increase in business for personal service providers in particular, such as those in the hospitality sector. With the global economy picking up and supply bottlenecks dissolving, the export-oriented German industry is expected to gain momentum too. While inflation will be higher in 2022 than it was in 2021, it will fall below the two-percent target in 2023, supporting private consumption. The poor start to 2022 means that overall, the German economy is likely to grow by 3.0 percent in 2022, less than previously expected. However, the pre-pandemic level of 2019 will likely be achieved by summer 2022. In 2023, global economic output is expected to grow by 2.9 percent.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook